Profibrillatory Structural and Functional Properties of the Atrial-Pulmonary Junction in the Absence of Remodeling - Gottlieb, Lisa A.; Belterman, Charly; van Amersfoorth, Shirley; Loyer, Virginie; Constantin, Marion; Hocini, Mélèze; Dekker, Lukas R. C.; Coronel, Ruben (Frontiers in Physiology, 2021)
Background: Sole pulmonary vein (PV) isolation by ablation therapy prevents atrial fibrillation (AF) in patients with short episodes of AF and without comorbidities. Since incomplete PV isolation can be curative, we tested the hypothesis that the PV in the absence of remodeling and comorbidities contains structural and functional properties that are proarrhythmic for AF initiation by reentry. Methods: We performed percutaneous transvenous in vivo endocardial electrophysiological studies and quantitative histological analysis of PV from healthy sheep. Results: The proximal PV contained more myocytes than the distal PV and a higher percentage of collagen and fat tissue relative to myocytes than the left atrium. Local fractionated electrograms occurred in both the distal and proximal PVs, but a large local activation (>0.75 mV) was more often present in the proximal PV than in the distal PV (86 vs. 50% of electrograms, respectively, p = 0.017). Atrial arrhythmias (run of premature atrial complexes) occurred more often following the premature stimulation in the proximal PV than in the distal PV (p = 0.004). The diastolic stimulation threshold was higher in the proximal PV than in the distal PV (0.7 [0.3] vs. 0.4 [0.2] mA, (median [interquartile range]), p = 0.004). The refractory period was shorter in the proximal PV than in the distal PV (170 [50] vs. 248 [52] ms, p < 0.001). A linear relation existed between the gradient in refractoriness (distal-proximal) and atrial arrhythmia inducibility in the proximal PV. Conclusion: The structural and functional properties of the native atrial-PV junction differ from those of the distal PV. Atrial arrhythmias in the absence of arrhythmia-induced remodeling are caused by reentry in the atrial-PV junction. Ablative treatment of early paroxysmal AF, rather than complete isolation of focal arrhythmia, may be limited to inhibition of reentry.